Growth of KNN Thin Films for Non‐Linear Optical Applications. Issue 4 (27th October 2017) - Sharma, Shweta; Gupta, Reema; Gupta, Vinay; Tomar, Monika
Abstract : Two‐wave mixing is a remarkable area of research in the field of non‐linear optics, finding various applications in the development of opto‐electronic devices, photorefractive waveguides, real time holography, etc. Non‐linear optical properties of ferroelectric potassium sodium niobate (KNN) thin films have been interrogated using two‐wave mixing phenomenon. Regarding this, a ‐axis oriented K0.35 Na(1‐0.35) NbO3 thin films were successfully grown on epitaxial matched (100) SrTiO3 substrate using pulsed laser deposition (PLD) technique. The uniformly distributed Au micro‐discs of 200 μm diameter were integrated with KNN/STO thin film to study the plasmonic enhancement in the optical response. Beam amplification has been observed as a result of the two‐wave mixing. This is due to the alignment of ferroelectric domains in KNN films and the excitement of plasmons at the metal–dielectric (Au–KNN) interface. Abstract : Non linear optical properties is interrogated in lead free ferroelectric Potassium Sodium Niobate (KNN) thin film on epitaxial matched STO substrate using two wave mixing technique. The phenomenon of beam amplification is observed which can be exploited for the fabrication of optical amplifiers.